Study of Chromogranin A Expression in Native and Cryopreserved Cell Culture of Adrenal Glands of Neonatal Piglets - Novikova, Oksana Yu.; Sidorenko, Olga S.; Bozhok, Galina A.; Bondarenko, Tatyana P. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 179